ICT-Supported Interventions Targeting Pre-frailty: Healthcare Recommendations from the Personalised ICT Supported Service for Independent Living and Active Ageing (PERSSILAA) Study - O’Caoimh, R. (2019)
Part of the Communications in Computer and Information Science book series (CCIS, volume 869)